Spectroscopy and micro-luminescence mapping of Xe-implanted defects in diamond - Deshko, Y.; Gorokhovsky, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Ion implantation in diamond creates optically active defects which have emission lines in broad spectral regions, and may be used in advanced photonics and optical communication applications. A brief review of the photoluminescence properties of Xe+ ion implanted diamond is presented. The Xe-related center is of particular interest as this center is one of a few centers (Ni, Si, Cr) in diamond having sharp emission lines in the infrared spectral region, specifically at 813 and 794 nm. The paper discusses an approach to determine an important and difficult to measure conversion efficiency of implanted ions into emitting optical centers. The method uses a micro- luminescence confocal mapping and statistical analysis based on a compound Poisson distribution, accounting for both the implanted centers and the optically excited centers statistics. Results of numerical simulations and experimental measurements are presented.